Musical performance and reception: eight centuries of troubadours and trouvères: the changing identity of medieval music - Haines, John (Cambridge Cambridge University Press, 2004)
From the medieval chansonniers to contemporary rap renditions, this book traces the changing interpretation of troubadour and trouvère music, a repertoire of songs which have successfully maintained public interest for eight centuries. A study of their reception, therefore, serves to illustrate the development of the modern concept of "medieval music". Important stages in their evolution include sixteenth-century antiquarianism; the Enlightenment synthesis of scholarly and popular traditions; and the infusion of archaeology and philology in the nineteenth century, leading to more recent theories on medieval rhythm.